Mercury nanoladders: a new method for DNA amplification, signal identification and their application in the detection of Hg(ii) ions. Issue 58 (21st June 2018) - Feng, Yuxiang; Shao, Xiangli; Huang, Kunlun; Tian, Jingjing; Mei, Xiaohong; Luo, Yunbo; Xu, Wentao
Abstract : A biosensor based on Hg(ii ) nanoladders integrated with graphene oxide (GO) for Hg(ii ) detection was developed. Abstract : A biosensor based on Hg(ii ) nanoladders integrated with graphene oxide (GO) for Hg(ii ) detection was developed. Nanoladders were essentially DNA sandwich structures supported by T–Hg(ii )–T and were used for Hg(ii ) trapping and signal translation. GO was used to differentiate the fluorescence generated by Hg(ii ) nanoladders from a background signal.